Assessment of sports talent children basis of individual typological approach - Kuramshin, Yu. F.; Dveyrina, O. A.; Terekhin, V. S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and scientifically substantiate a model for assessing sports talent during sports orientation and selection based on an individual typological approach.Methods and structure of the study. The scientific experiment was carried out on the basis of the Center for testing, selection and support of sports gifted children of the Lesgaft National State University of Physical Education, Sports and Health, St. Petersburg. In the course of the study, a comprehensive assessment of general and special sports predisposi-tion was used, consisting of genetic, morphofunctional, psychological and motor criteria.Results and conclusions. A model for assessing sports talent during sports orientation and selection based on an individual typological approach has been developed, which includes three main blocks: medical and biological, psychologi-cal and sports and pedagogical. The model was tested on various contingents of the examined - children of preschool and school age and athletes. The results of its experimental verification confirmed the effectiveness of this approach to assess-ing sports abilities and their originality.